The effect of land management and organic matter inputs on bacterial population and soil nutrients across different types of agroforestry system - MAYDELLA VISTA PUTRI RINADY; YULIA NURAINI; CAHYO PRAYOGO; NOVI ARFARITA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rinady MVP, Nuraini Y, Prayogo C, Arfarita N. 2023. The effect of land management and organic matter inputs on bacterial population and soil nutrients across different types of agroforestry system. Biodiversitas 24: 1333-1345. Different management of agroforestry systems changes crop composition and growth. This will affect organic matter inputs that become the source of food and energy for soil microorganisms. The soil organisms themself play an important role in amplifying soil biogeochemical processes and regulating soil reactions. This process allows the nutrients to be released into the soil and absorbed by the crop. This study aimed to examine the abundance of soil bacterial population and the changes in soil chemical properties (soil pH, total soil organic carbon (C), and total soil N (Nitrogen) under different land management and organic matter inputs. The determination of total organic C and total soil N was used by Walkey and Black and Kjedahl methods. Total Plate Count (TPC) techniques were employed to measure Total Bacteria Population (TBP) and Total Cellulolytic Bacteria (TCB). The Randomized Complete Block Design was used along with the 5% Tukey's test to examine the significant effect of the treatments. These treatments consisted of various agroforestry system as follow: (i) pine-coffee agroforestry system (PK), (ii) pine-banana agroforestry system (PPs), (iii) pine-cardamom agroforestry system (PR), (iv) pine-vegetable agroforestry system (PS), (v) mixed garden (KC), and (vi) citrus (LJ). Each treatment was repeated four times to obtain 24 experimental plots using a size of 20 m x 20 m. The results showed that the highest organic C and N content was obtained at the PK (agroforestry of pine at 41 years and coffee at 11 years old) plot, which was about 6.64% and 0.56%. Those parameters strongly correspond to the greatest soil bacteria population and soil cellulolytic bacteria population at the value of 1,71 x 105 CFU/g and 4,24 x 104 CFU/g, resulting from the greatest quantity of in-situ litter accumulation at PK plot to reach about 201.35 g. The dry weight value of litter in situ at the PK plot is greater than that of the PS and LJ plots by 81% and 87%. A power equation followed the relationship between soil organic C and the total bacteria population. A similar trend has been observed between total soil Nitrogen and total bacteria population. We concluded that changes in different management could affect soil chemical conditions and the changes in the total population of soil bacteria and cellulolytic soil bacteria.